Effectiveness of antenatal exercise counseling module on knowledge and self-efficacy among nurses in Kelantan - Ismail @ Yaakub, Nor Azura (2018)
Background: Recent recommendation by the American College of Obstetrics and Gynaechologist recommends that women with non-complicated pregnancy to engage in 150 minutes per week of moderate-intensity aerobic exercise. The healthcare providers should have adequate knowledge and self-efficacy in the process of counseling. Objectives: To determine the effectiveness of antenatal exercise counseling module on knowledge and self efficacy between control and intervention groups at baseline and 4 weeks post intervention among staff nurses in Kelantan. Methods: A community-based interventional study was conducted involving 132 participants were recruited from the Maternal and Child Health Clinic whom did not practise antenatal exercise counseling. The control and intervention groups each consist of 66 nurses randomly selected from Pasir Mas and Tumpat districts, respectively. The intervention group received antenatal exercise counseling module while the control group were free to do self-reading on antenatal exercise. Assessment on knowledge and self-efficacy on antenatal exercise were done at baseline and 4 weeks post intervention. Repeated measure ANCOVA was used to analyse the mean score difference of both groups at baseline and post intervention. Results: At baseline, there were no significant differences in the mean score of knowledge scores (p 0.827) and self-efficacy scores (p 0.089) between the intervention and control groups. There was significant difference in knowledge scores between intervention and control groups between baseline and 4-weeks post intervention after controlling for duration of practice and formal training received (p <0.001). There was significant difference in self-efficacy scores between intervention and control groups between baseline and 4-weeks post intervention after controlling for duration of practice and formal training received ( p 0.005). Conclusion: The antenatal exercise counseling module found to be effective in improving nurses’ knowledge and self-efficacy in antenatal exercise counseling.